Women’s experiences with antibiotic use in urinary tract infections: Insights from the patient’s perspective - Jovanović, Aleksandar; Drobac, Milica; Tadić, Ivana; Vidović, Bojana; Pavlović, Dragana; Veličković Radovanović, Radmila; Odalović, Marina; Kundalić, Ana; Džodić, Predrag; Krajnović, Dušanka (Archives of Pharmacy, 2025)
From patients’ perspective, the use of antibiotics to treat urinary tract infections (UTIs) in Serbia is unexplored, and therefore the aim of this study is to examine antibiotic use among these patients. An online cross-sectional study using snowball sampling was conducted during the winter of 2020/21 using a validated Google Docs questionnaire. The study included 236 female patients with a mean age of 34.9 ± 14.2 years. Most of the patients perceived UTI symptoms as severe (62.3%) and disruptive for their daily routines (51.3%). The majority of the patients (77.1%) used antibiotics by doctors’ prescriptions. Other patients used antibiotics on their own and their selection. Self-treatment with antibiotics was associated with perceived symptom severity (p=0.006) and residence (p=0.017). In total, 17 different antibiotics were reported as being used for UTI treatment and the most frequent were fluoroquinolones (30.3%), cephalosporins (21.2%), and sulfonamides (15.7%). The highest consistency with national and European guidelines in doctors’ decisions on antibiotic therapy was observed for treating UTIs in pregnant women (80.0%). These findings emphasize the need for education of healthcare professionals and clinical practice improvement in making rational antibiotic prescribing decisions.